Referral of patients with cancer to palliative care: Attitudes, practices and work‐related experiences among Swedish physicians. (14th August 2022) - Adolfsson, Karin; Kreicbergs, Ulrika; Bratthäll, Charlotte; Holmberg, Erik; Björk‐Eriksson, Thomas; Stenmarker, Margaretha
Abstract: Objective: This study aimed to explore the attitudes, practices and work‐related experiences among Swedish physicians regarding the referral process, integration and transition between oncology care and palliative care (PC). Methods: A cross‐sectional online survey was performed with a study‐specific questionnaire in 2016–2017 in south‐eastern Sweden. Physicians working with cancer patients within surgical specialties, medical specialties and paediatric oncology participated. Results: The vast majority of the 130 participating physicians (99.2%) stated that PC was beneficial for the patient and were positive about early integration of PC (65.5%). Still, only 27.6% of the participants introduced PC at an early stage of non‐curable disease. However, paediatric oncologists had a very early introduction of PC in comparison with medical specialties ( p = 0.004). Almost 90% of the study population said they wanted to know that the patient had been taken care of by another care facility. Conclusions: Despite the physicians' positive attitude towards early integration and referral to PC, they often acted late in the disease trajectory. This late approach can reduce the patient's opportunity of improving quality of life during severe circumstances. There is a need for in‐depth knowledge of the physicians' challenges in order to bridge the gap between intentions and actions.